Status of Professional Skills in MBA Graduates, Its Challenges, and Way Forward in Kathmandu Valley: Evidence from Professional Skill Index - Bhandari , Udbodh; Rana, Malati; Devkota, Niranjan; Parajuli, Seeprata; Poudel, Udaya (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Today's MBA courses are continuous preparation-based teaching-learning practice to meet the requirements that industries expect from MBA graduates and further enhance their skills and knowledge that would aid them to fit in the job market. Thus, this study tries to assess the status of professional skills in MBA graduates, its challenges, and the way forward with the help of a professional skill index. Based on descriptive analysis, this study is conducted among 280 employers who employ MBA graduates, and a structured questionnaire was applied to collect information. The purposive sampling method was used to select the samples of 280. The study is conducted in Kathmandu valley as many MBA colleges and banks, finance companies, insurance companies, industries, and many private companies are located in Kathmandu valley. So, the graduates also choose Kathmandu valley in the maximum number to pursue their further career. The study's findings revealed that professional skills are generally looked up into hard skills and soft skills, and 100% of organizations look for professional skills possessed by candidates while hiring them. However, they give 100% attention to soft skills possessed by MBA graduates and 99.2% attention to hard skills possessed. In soft skills, an organization thinks communication skills are must by graduates, whereas they prioritize typing skills hard skill. Therefore, this study concludes that MBA students and colleges should focus on enhancing graduates' communication skills. Likewise, being in today's computerized business world typing skill is a must for graduates. Finally, MBA graduates must develop professional attributes among themselves to fit in today's job market